Effectiveness of aromatherapy with lavender compared to progressive muscle relaxation on anxiety and vital signs in patients under spinal anesthesia: A randomized clinical trial - Nazanin Amini; Safoora Omidvar; Masoomeh Noruzi Zamenjani; Mehdi Harorani; Hesameddin Modir (Wolters Kluwer Medknow Publications, 2024)
Objective: This study aimed to determine the effectiveness of aromatherapy with lavender essential oil compared to progressive muscle relaxation (PMR) on anxiety and vital signs of patients under spinal anesthesia. Materials and Methods: This clinical trial was conducted on 120 spinal anesthesia candidates who were randomly assigned into three groups of 40 including control, PMR (Jacobsen group), and aromatherapy. The state-trait anxiety inventory was completed on surgery day and 15 min after the end of the intervention by the samples of all three groups, and at the same time as completing the questionnaire, vital signs were also measured and recorded. Results: The mean score of anxiety after intervention was lower than that before the intervention in the aromatherapy group (P < 0.001). The mean score of anxiety in the aromatherapy group was significantly lower than that in the Jacobsen group (P < 0.001). Moreover, data analysis showed a significant decrease in the mean arterial blood pressure scores of the PMR (P = 008) and aromatherapy (P < 0.001) groups and a statistically significant increase in the mean heart rate scores in the control group (P = 0.002). Conclusion: The use of aromatherapy with lavender is more effective than PMR therapy in reducing the anxiety level of patients undergoing spinal anesthesia. Due to the high level of anxiety and its serious effects on the patient's hemodynamics, aromatherapy with lavender can be used as an easy and cheap method to reduce anxiety in operation rooms.